Concessões de rodovia: o caso da Rodovia Dutra - Neves, Luciana Gomes (2008)
The road of concessions had been solution found for the public sector as form to provide the necessary resources for construction and manutenance with national road infrastructure. However, the concessions had been initiated directly in a regulatório landmark environment inexistent being fiscalized for the power concessions, through the old DNER. Additionally the inexistence of a regulation landmark the Brazilian road granted to the private initiative possess the characteristic to be opened road, possessing diverse entrances and exist, what it means one high cost of if closing all the accesses. This system, the toll payment is carried through in case that the using pass for the square of toll, independent of the distance covered in the road. Such inefficiency of collection has supplanted efforts to become the toll collection more joust. The objective of this work is to analyze the decurrent problems of the alteration possibility or creation of toll squares as form to apply the principle of tariff justice and to allow more reasonable tariffs for the users. For in such a way, the regulation of natural monopolies and the decurrent problems of the presence of anti-symmetrical information are presented the related boardings. After that, a revision of the financing of the national road infrastructure becomes, is told the first concessions, the conceptual an legal function of the regulation agency and adopted aspects in the concession contract. Finally, the case of the Dutra Road is analyzed where already alterations of the configuration of the way waked up in contract had been granted and exist of the new configuration. One concludes that the regulation of the road concessions still is a process in construction phase and learn being devoid of a quarrel on the use that if makes of the highway for the community of close.